Dynamic advancements in teaching and learning based technologies : new concepts - Ng, Eugenia M. W., 1959-; Karacapilidis, Nikos, 1967-; Raisinghani, Mahesh S., 1967- (Hershey PA : Information Science Reference, 2011)
'This book explores the impact of Web-based technology on the design, implementation and evaluation of the learning and teaching process, as well as the development of new activities, relationships, skills, and competencies for the various actors implied in such processes'--Provided by publisher
Includes bibliographical references (p. 354-394) and index.
Keywords: Web-based instruction